Baricitinib Attenuates Autoimmune Phenotype and Podocyte Injury in a Murine Model of Systemic Lupus Erythematosus - Lee, Jaeseon; Park, Youngjae; Jang, Se Gwang; Hong, Seung-Min; Song, Young-Seok; Kim, Min-Jun; Baek, SeungYe; Park, Sung-Hwan; Kwok, Seung-Ki (Frontiers in Immunology, 2021)
Objective: Baricitinib, a selective inhibitor for janus kinase (JAK) 1 and JAK2, is approved for use in rheumatoid arthritis. Systemic lupus erythematosus (SLE) is recently regarded as a potential candidate targeted by JAK inhibitors because of the relationship between its pathogenesis and JAK/signal transducer and activator of transcription (STAT) pathway-mediated cytokines such as type I interferons. The objective of this study was to determine whether baricitinib could effectively ameliorate SLE using a murine model Methods: To investigate effects of baricitinib on various autoimmune features, especially renal involvements in SLE, eight-week-old MRL/Mp-Faslpr (MRL/lpr) mice were used as a lupus-prone animal model and treated with baricitinib for eight weeks. Immortalized podocytes and primary podocytes and B cells isolated from C57BL/6 mice were used to determine the in vitro efficacy of baricitinib. Results: Baricitinib remarkably suppressed lupus-like phenotypes of MRL/lpr mice, such as splenomegaly, lymphadenopathy, proteinuria, and systemic autoimmunity including circulating autoantibodies and pro-inflammatory cytokines. It also modulated immune cell populations and effectively ameliorated renal inflammation, leading to the recovery of the expression of structural proteins in podocytes. According to in vitro experiments, baricitinib treatment could mitigate B cell differentiation and restore disrupted cytoskeletal structures of podocytes under inflammatory stimulation by blocking the JAK/STAT pathway. Conclusions: The present study demonstrated that baricitinib could effectively attenuate autoimmune features including renal inflammation of lupus-prone mice by suppressing aberrant B cell activation and podocyte abnormalities. Thus, baricitinib as a selective JAK inhibitor could be a promising therapeutic candidate in the treatment of SLE.